ANALISIS PENGARUH MOTIVASI DAN STRES KERJA TERHADAP KEPUASAN KERJA (STUDI PADA PEGAWAI PUSKESMAS KEDUNGADEM KECAMATAN KEDUNGADEM KABUPATEN BOJONEGORO) - NERRISSA ARVIANA KUSUMA, NADIA (Jurnal Ilmu Manajemen (JIM), 2017)
Puskesmas is a technical implementation unit under the supervision of the Regency/City Service. Puskesmas is also the front guard in conducting health efforts in the deeper scope of yag that is within the scope of the kecamatan. Puskesmas Kedungadem is one of the many puskesmas in Indonesia which is located in Bojonegoro. As the spearhead of the health care system in Indonesia, the puskesmas is responsible for carrying out public health services well and can satisfy the whole community, especially the residents of the sub-district. Motivation and job stres is an important factor to generate employee job satisfaction that impact on the satisfaction of health services for all communities.This type of research is a descriptive research with quantitative approach that aims to develop and use mathematical models, theoretical, and hypothesis related to the phenomenon. This research was conducted on all health personnel with details of 32 civil servants and 11 PTT. The data were collected by giving questionnaires and direct interviews with the leaders of puskesmas. Data analysis techniques used by researchers are Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Analysis, Hiotesis Test, and Determination Coefficient Test. This research procedure starts from the pre-field stage, field study, data analysis, and conclusion.Result of data analysis from this research that is (1) Motivation have positive significant effect to employee job satisfaction with tcount value 3,642 and significance value 0,001. (2) Job stres has a significant negative effect on employee job satisfaction with tcount value of -3.875 and significance value of 0.000. (3) Motivation and job stres affect the employee job satisfaction with the value of Fhitung amounted to 30.257 and the significance value of 0.000 Keywords: Motivation, Job Stress, dan Job Satisfactio